One Small Step for Man: Change and Continuity in Perceptions and Enactments of Homosocial Intimacy among Young Australian Men. (April 2020) - Ralph, Brittany; Roberts, Steven
While recent scholarship has documented a growth of same-sex, nonsexual kissing among young men in Western societies, this may reflect a weakening, rather than complete transformation, of hegemonic gender structures. Critically engaging with current theorizing of "inclusive masculinities, " this article reports the findings from a study of young Australian men's views on what constitutes acceptable forms of homosocial intimacy and how they attach meaning to these behaviors. Using qualitative data from focus groups with twenty-two men from five different subcultural peer groups and eight follow-up individual interviews, we illustrate that exaggerated intimate behaviors are not considered authentic displays of affection, and therefore do not meaningfully challenge gendered power structures. Rather, they have been adopted into the repertoire of ways men can perform masculinity. However, this hybridity is neither a means of reconfiguring male power, nor evidence of entirely inclusive masculinities, but instead constitutes an initial step toward inclusivity.